Experimental Demonstration of 1 μm Dual-Wavelength Fiber Laser Based on Cascade Single-Stage Resonant Cavity - Xinran Li; Yun Ye; Ke Li; Xinyi Ding; Hanshuo Wu; Xiaolin Wang; Weihong Hua (IEEE Photonics Journal)
Dual-wavelength fiber lasers (DWFL) have tremendous application prospects in industrial processing, electronic countermeasures, biomedicine and so on due to their advantages of flexible dual-wavelength output. In this work, we have constructed a 1 μm dual-wavelength fiber laser based on a cascaded resonant cavity with fiber Bragg gratings (FBGs), and the dual-wavelength laser output at the central wavelengths of 1060 nm and 1080 nm was simultaneously achieved. The laser performance involving output power and spectral evolution of this dual-wavelength fiber laser were carefully compared and investigated under two different cascading configurations, including 1060-1080 and 1080-1060. The experimental results reveal that the 1060-1080 configuration was more favorable for the dual-wavelength fiber lasers to generate high-power and high-spectral-purity dual-wavelength laser compared to the 1080-1060 configuration. Furthermore, based on the 1060-1080 configuration, a continuous-wave dual-wavelength laser output at 1060 nm with 40.43 W and 1080 nm with 302.65 W was simultaneously achieved, with the nonlinear effect suppression over 40 dB at the maximum power. To the best of our knowledge, this is the first demonstration of 1 μm cascaded resonant cavity dual-wavelength fiber laser. This work offers a significant guidance for designing and implementing the high-power compactness dual-wavelength fiber laser within 1 μm spectral region.